2009
DOI: 10.1007/s11426-009-0002-6
|View full text |Cite
|
Sign up to set email alerts
|

Enantiopure inherently chiral calix[4]arene derivatives containing quinolin-2-yl-methanol moiety: Synthesis and application in the catalytic asymmetric addition of diethylzinc to benzaldehyde

Abstract: A series of novel N,O-type chiral ligands derived from enantiopure inherently chiral calix[4]arenes containing quinolin-2-yl-methanol moiety in the cone or partial-cone conformation have been synthesized and characterized. Moreover, they have been applied to the catalytic asymmetric addition of diethylzinc to benzaldehyde, which represents the first example that the inherently chiral calixarene can be used as the chiral ligands for the catalytic asymmetric synthesis.inherently chiral calixarenes, synthesis, N,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Calix [4]arenes, as one of the most important supramolecular building blocks, can be useful in ion and metal complex because of their suitable scaffold for the development of new bulky and structurally well-defined ligands [10][11][12][13][14][15]. Combination of calixarene cavity with chiral catalytic centre or inherent chirality [16,17] might lead to multifunctional supramolecular asymmetric catalyst [18]. Recently, we have demonstrated that proline based on calix [4]arene scaffold can catalyze the enantioselective direct aldol reactions with good-to-excellent enantioselectivities [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Calix [4]arenes, as one of the most important supramolecular building blocks, can be useful in ion and metal complex because of their suitable scaffold for the development of new bulky and structurally well-defined ligands [10][11][12][13][14][15]. Combination of calixarene cavity with chiral catalytic centre or inherent chirality [16,17] might lead to multifunctional supramolecular asymmetric catalyst [18]. Recently, we have demonstrated that proline based on calix [4]arene scaffold can catalyze the enantioselective direct aldol reactions with good-to-excellent enantioselectivities [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…1368 chiral calix [4]arenes containing quinolin-2-yl-methanol moiety. 2 According to the proposed mechanistic mode by Deng and co-workers, 15 we believe that the aldehyde is activated by the hydroxyl group through hydrogen bonding, while the nitromethane is activated by the tertiary amino group in 5a or 5b catalytic process (Scheme 2). The more beneficial effect of the protic solvent, especially the mixed solvent EtOH/H 2 O, may be plausibly explained that they can effectively stabilize nitromethide anion and nitro aldol product through hydrogen bonding interaction.…”
Section: Synthesis Of No-type Inherently Chiral Calixmentioning
confidence: 99%
“…To mimic enzymatic catalysis process and develop efficient chiral catalysts, a variety of inherently chiral calix [4]arenes substituted at the meta position and the upper rim have been applied as chiral organocatalysts in aldol reaction, 1 addition of diethylzinc to benzaldehyde, 2 Michael addition [3][4][5][6][7] and alkylation of a glycine derivative. 7 And the highest ee in these catalytic reactions is up to 31%.…”
Section: Introductionmentioning
confidence: 99%
“…The catalytic results indicated that these chiral ligands could catalyze the asymmetric addition of diethylzinc to benzaldehyde with high catalytic activity, although the enantioselectivity was low [70]. …”
Section: Applications Of Inherently Chiral Calixarenesmentioning
confidence: 99%